EMPLOYMENT OF EVACUEES TO KHOREZM DURING THE SECOND WORLD WAR - Allaberganov Sherali Yuldashevich (Scholar Express Journal, 2024)
This article provides information about the workers evacuated to Khorezm during the Second World War, their employment based on their profession, and the assistance provided to the evacuated population
Keywords: evacuation; Ukraine; Belarus; Moldavia